Congenital absence of the bilateral long heads of the biceps brachii tendons in a patient with Silver-Russell syndrome - Nathan Markus, BS; Andrew B. Ross, MD, MPH; Teresa T. Martin-Carreras, MD (Radiology Case Reports, 2023)
Agenesis of the long head of biceps tendon (LHBT) is a congenital anomaly not commonly reported in the literature, and bilateral absence of the LHBT is even more rare. Most cases of LHBT agenesis are found incidentally at arthroscopy or are diagnosed by magnetic resonance imaging after a history of insidious shoulder pain or anterior shoulder instability. We present the magnetic resonance imaging findings of bilateral congenital absence of the LHBT in a 37-year-old male with Silver-Russell syndrome who presented with progressive, bilateral anterior shoulder pain after failing conservative treatment strategies. This case report describes bilateral agenesis of the LHBT in association with a congenital growth disorder that has not been described previously in the literature. We provide a description of key MR imaging findings to assist in making the diagnosis, along with a discussion of potential differential diagnoses, and a review of the current literature on this topic.